1981
DOI: 10.1139/x81-120
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of plant biomass based on the allometric equation

Abstract: Estimation of the parameters in the allometric equation by fitting a simple linear regression to the logarithmically transformed variables results in biased estimates of the arithmetic mean. This bias expressed as a percent of the mean approaches the limit −(1 − e−σ2/2) (100) as n increases. An adjusted estimator developed by Finney rather than the one given by Baskerville should be used when s2 is large and n is small. A change of measurement scale of the x or y variables presents no difficulty, but problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…For the purposes of the present study, a and b values are reported for the biased regression, in conjunction with the correction factor as given by Sprugel (1983). Yandle and Wiant (1981) reported that the bias B = (Yc -Y)/Yc, as a percent of the unbiased estimate is…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purposes of the present study, a and b values are reported for the biased regression, in conjunction with the correction factor as given by Sprugel (1983). Yandle and Wiant (1981) reported that the bias B = (Yc -Y)/Yc, as a percent of the unbiased estimate is…”
Section: Discussionmentioning
confidence: 99%
“…This inherent bias has been reported by Finney (1941), but concern for its potential impact on biomass estimates was described in Madgwick (1970), Mountford and Bunce (1973) and Sprugel (1983). Several techniques for correcting the bias in logarithmic regression estimates have been reported (Baskerville 1972;Beauchamp and Olson 1973;Yandle and Wiant 1981;Sprugel 1983). For example, according to Baskerville (1972)…”
Section: Discussionmentioning
confidence: 99%
“…Although this inherent bias has long been recognised [7], concern of its potential impact on estimates of biomass is relatively recent [10,15,26]. Several procedures for correcting bias in logarithmic regression estimates have been advocated [2,3,26,33].…”
Section: Regression Analysismentioning
confidence: 99%
“…Yandle and Wiant [33] reported that the bias , as a percent of the unbiased estimate equals to Percent bias = ((e CF -1)/e CF )100 (2) and is constant over the range of X values. Wiant and Harner [32] suggested that it is informative to express the standard error of for a given X as a percent of .…”
Section: Regression Analysismentioning
confidence: 99%
“…Come noto, tale trasformazione, pur consentendo di effettuare una regressione lineare attraverso la tra dizionale tecnica dei minimi quadrati, introduce, nella successiva fase di ri-trasformazione dei dati, un errore sistematico che richiederebbe l'impiego di un fattore di correzione calcolato attraverso l'errore standard (Yandle & Wiant 1981, Sprugel 1983.…”
Section: Peso Seccounclassified